2016
DOI: 10.3390/molecules21080974
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Bioactivity Relationships of Methylxanthines: Trying to Make Sense of All the Promises and the Drawbacks

Abstract: Abstract:Methylxanthines are a group of phytochemicals derived from the purine base xanthine and obtained from plant secondary metabolism. They are unobtrusively included in daily diet in common products as coffee, tea, energetic drinks, or chocolate. Caffeine is by far the most studied methylxanthine either in animal or epidemiologic studies. Theophylline and theobromine are other relevant methylxanthines also commonly available in the aforementioned sources. There are many disseminated myths about methylxant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
151
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(151 citation statements)
references
References 347 publications
0
151
0
Order By: Relevance
“…Methylxanthines increases cAMP by inhibiting the phosphodiesterase enzymes (PDEs), however not all the methylxanthines act by this way. The increase in cyclic AMP also depends on the dose of the drugs used and their potency [2,6]. In our study, some drugs such as IBMX, caffeine, theophylline and pentoxifylline showed a significant increase in cyclic AMP in zebrafish embryos.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…Methylxanthines increases cAMP by inhibiting the phosphodiesterase enzymes (PDEs), however not all the methylxanthines act by this way. The increase in cyclic AMP also depends on the dose of the drugs used and their potency [2,6]. In our study, some drugs such as IBMX, caffeine, theophylline and pentoxifylline showed a significant increase in cyclic AMP in zebrafish embryos.…”
Section: Resultsmentioning
confidence: 58%
“…They are heterocyclic organic compounds consisting of pyrimidinedione and imidazole rings coupled with each other [1]. Methylxanthines are phytochemicals found in plants such as coffee, tea, mate, kola nuts and cacao beans [2]. Thus far, seven natural methylxanthines have been identified: aminophylline, caffeine, IBMX, paraxanthine, pentoxifylline, theobromine and theophylline [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Liu et al , 2014; Liu et al , 2013). Molecular SARs have been extensively and successfully used in the field of drug discovery and development (Akhtar et al , 2016; Cordomi et al , 2016; Monteiro et al , 2016; Putz et al , 2016; Sharma et al , 2016). Likewise the ultimate goal of developing nano-SARs is to enable prediction of toxicity based on ENM intrinsic physicochemical properties and thus enable safer by design development of commercial ENMs.…”
Section: Intrinsic Properties Of Ienmsmentioning
confidence: 99%